2021
DOI: 10.1002/jcsm.12806
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, feasibility trial of an exercise and nutrition‐based rehabilitation programme (ENeRgy) in people with cancer

Abstract: Background Despite rehabilitation being increasingly advocated for people living with incurable cancer, there is limited evidence supporting efficacy or component parts. The progressive decline in function and nutritional in this population would support an approach that targets these factors. This trial aimed to assess the feasibility of an exercise and nutrition based rehabilitation programme in people with incurable cancer. Methods We randomized community dwelling adults with incurable cancer to either a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 30 publications
1
23
0
1
Order By: Relevance
“…In terms of goal attainment, >70% of users were able to achieve their step goals in this trial, and the average step count (approximately 3000-3500 per day) was comparable with that found in other studies with patients in active cancer treatment [9,[33][34][35]. Although these results might underestimate participants' real step counts (as these had to be manually claimed each day), they suggest that users are interested in tracking their physical activity, particularly their step counts.…”
Section: Principal Findingssupporting
confidence: 81%
“…In terms of goal attainment, >70% of users were able to achieve their step goals in this trial, and the average step count (approximately 3000-3500 per day) was comparable with that found in other studies with patients in active cancer treatment [9,[33][34][35]. Although these results might underestimate participants' real step counts (as these had to be manually claimed each day), they suggest that users are interested in tracking their physical activity, particularly their step counts.…”
Section: Principal Findingssupporting
confidence: 81%
“…This also combines well with the publication of the ENERGY trial, a multi-modal intervention study in palliative cancer patients that has shown an adherence to a physical and nutrition intervention of greater than 80%. It also suggests that this intervention showed a lower mean incremental cost, suggesting it saved money compared to standard care [79].…”
Section: Multi-modal Interventionmentioning
confidence: 98%
“…A multimodal approach seems feasible in patients with advanced cancer, as addressed by some studies. Combinations of physical exercise (ET and/or RT) with nutritional supplements containing omega-3 fatty acids (EPA or docosahexaenoic acid) [ 80 , 81 ] or branched-chain amino acids [ 82 , 83 ] or just nutritional counselling and dietary adjustments as needed [ 84 ] were safe approaches in this population, with some positive results in improving protein intake and muscle strength and reducing symptoms like nausea e vomiting. These results must yet be confirmed in more robust and phase III trials.…”
Section: Multimodal Approach In Cachexiamentioning
confidence: 99%